Computational Models for Multiparty Turn-Taking - Bohus, Dan; Horvitz, Eric (Microsoft, 2010)
We describe a computational framework for modeling and managing turn-taking in open-world spoken dialog systems. We present a representation and methodology for tracking the conversational dynamics in multiparty interactions, making floor control decisions, and rendering these decisions into appropriate behaviors. We show how the approach enables an embodied conversational agent to participate in multiparty interactions, and to handle a diversity of natural turn-taking phenomena, including multiparty floor management, barge-ins, restarts, and continuations. Finally, we discuss results and lessons learned from experiments.